Comparison of Matrigel and Matriderm as a carrier for human amnion-derived mesenchymal stem cells in wound healing. (December 2016) - Tuca, Alexandru-Cristian; Ertl, Juliane; Hingerl, Kerstin; Pichlsberger, Melanie; Fuchs, Jakob; Wurzer, Paul; Pfeiffer, Dagmar; Bubalo, Vladimir; Parvizi, Daryousch; Kamolz, Lars-Peter; Lang, Ingrid
Abstract: Amnion-derived mesenchymal stem cells (AMSC) are a promising tool in regenerative medicine. Here we evaluated the utility of Matrigel and Matriderm as carrier for the topical application of AMSC to mice skin wounds. In both application forms, AMSC promoted neovascularization of the wound area. Matrigel proved as excellent matrix for AMSC and immigrating mouse cells, but the solid Matriderm enabled a more adequate positioning of AMSC into the wound. Although AMSC did not attach to Matriderm, they reliably induced wound reduction. Thus, a combined administration of AMSC/Matriderm could be beneficial to potentiate the encouraging effects on wound healing. Highlights: Amnion-derived mesenchymal stem cells (AMSC) promote wound healing in mice. The application method of AMSC affect the efficiency of re-epithelialization. Matrigel as carrier for AMSC has excellent cell-supplying properties. Matriderm as carrier for AMSC allows easy positioning to the wound. A combined administration of AMSC/Matriderm may potentiate wound healing.